Labour and the wage : a critical perspective - Adams, Zoe, 1991- (Oxford : Oxford University Press, 2020)
This book examines the problem of wage security and clarity of employment in labour law. It studies the neoclassical and institutional models of labour law, and the wage. It concludes that the way the wage is treated in labour law theory is dependent upon the way legal concepts themselves are conceptualized by their users.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 1, 2020).
Keywords: Labor laws and legislation -- Social aspects; Wages -- Law and legislation; Economics -- Sociological aspects